Effectiveness of Implementing the STAD Type Cooperative Learning Model Through Modifying Net and Field Media on the Volleyball Learning Outcomes - Heru Sulistiadinata (Journal of Physical and Outdoor Education, 2025)
This study aims to determine the effectiveness of the implementation of the Student Teams-Achievement Divisions (STAD) cooperative learning model through modifications to the net and field media on the volleyball learning outcomes of junior high school students in Cimahi City. The research method used a quasi-experimental design with a pretest-posttest control group design approach. The study population was 60 students with a sample of 60 people using a total sampling technique, divided into an experimental group (n = 30) and a control group (n = 30). The research instrument used a volleyball skills test covering passing, serving, and playing with high validity and reliability (α = 0.89). The data analysis technique used a paired t-test and an independent t-test with α = 0.05. The results showed a significant increase in the experimental group from an average of 65.23 to 82.67. while the control group from 64.87 to 72.43. The independent t-test showed a significant difference (t=7.896; with a difference of 10.24 points. It can be concluded that the STAD learning model through net and field media modifications is effective in improving volleyball learning outcomes for junior high school students in Cimahi City.